Faktor-faktor yang Berpengaruh terhadap Semangat Kerja Guru dalam Melaksanakan Tugas Jabatan di Sekolah Dasar - Bambang Budi Wiyono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Factors Affecting Teachers' Morale in Doing Their Professional Tasks at the Elementary Schools. The study attempted to describe teachers' morale and factors affecting the teachers' morale to do their professional tasks. The sample consisted of 300 teachers of the public elementary schools in Yogyakarta taken by cluster proporsional random sampling. The data were gathered by questionnaires, interview and documentary, and then analyzed statistically by mean and standard deviation. The results showed that the mean of teachers' morale was 147.33 with standard deviation 9.62. It means that the teachers had a high morale to do their professional tasks. There were positive influences of school condition, principal leadership, education and salary of teachers, but there were no influences of work period and profession level to the teachers'morale to do their professional tasks.